Comparison of Corneal Biomechanical Properties among Axial Myopic, Nonaxial Myopic, and Nonmyopic Eyes - Tubtimthong, Aratchaporn (Biomed Res Int, 2020)
PURPOSE: To compare corneal deformation characteristics using ultra-high-speed Scheimpflug camera (Corvis ST) in patients with nonmyopic (NM), mild-to-moderate nonaxial myopic (MM), and high axial myopic (HM) eyes. METHODS: In this cross-sectional study, normal subjects aged >40 years with no history of ocular laser/surgery were classified according to axial length (AL) and spherical equivalence (SE) into three groups: (1) NM (SE > −0.50 D and AL < 26 mm), (2) MM (SE −6.00 D to −0.50 D and AL < 26 mm), and (3) HM (SE ≤ −6.00 D and AL ≥ 26 mm). Seven parameters including corneal deformation amplitude (CDA), inward/outward corneal applanation length, inward/outward corneal velocity (ICV and OCV), peak distance, and radius were measured. Pearson correlation and linear mixed-effects model were done. RESULTS: A total of 180 eyes were recruited. 98 eyes were NM, 30 eyes were MM, and 52 eyes were HM. There were significant correlations of OCV to the degree of refractive error (r = 0.203, p < 0.001) and AL (r = −0.242, p < 0.001). After adjusting for age, sex, intraocular pressure, and corneal thickness, there was significantly higher CDA (β = 0.07, p < 0.001), faster OCV (β = −0.08, p < 0.001), and smaller radius (β = −0.39, p=0.01) in the HM group compared to the NM group. CONCLUSION: The higher CDA, faster OCV, and smaller radius found in the HM may suggest that these eyes have reduced ocular stiffness and may be less stable and more prone to stress.